A stress paradox: the dual role of the unfolded protein response in the placenta - Chowdhury, Diba; Jang, Chloe E.; Lajoie, Patrick; Renaud, Stephen J. (Frontiers in Endocrinology, 2024)
The placenta is a temporary organ that forms during pregnancy and is essential for fetal development and maternal health. As an endocrine organ, proper placental function requires continual production, folding, and transport of proteins and lipids. Central to these processes is the endoplasmic reticulum (ER), a dynamic organelle responsible for maintaining cellular protein and lipid synthesis and processing. ER stress occurs when there is an accumulation of unfolded or misfolded proteins, which triggers the activation of cellular pathways collectively called the unfolded protein response. Unfolded protein response pathways act to alleviate the misfolded protein burden and restore ER homeostasis, or if unresolved, initiate cell death. While prolonged ER stress has been linked to deficient placental function and adverse pregnancy outcomes, basal activation of unfolded protein response pathways is required for placental development and function. This review explores the importance of ER homeostasis in placental development and function, examining how disruptions in ER stress responses may contribute to adverse pregnancy outcomes.